The Influence and Limitations of AI in Cybersecurity Domain - Ikromjon Tojiboyev; Nuriddin Safoev (Zien Journals, 2023)
The use of artificial intelligence (AI) is creating new opportunities for creating value in businesses, industries, communities, and society as a whole. As technology has become increasingly relevant in many aspects of the world, it has been integrated into various industries, including cybersecurity. With the growing importance of information technology in businesses, cybersecurity has become crucial to protect data and information. AI has been heavily influencing cybersecurity on a large scale, and machine learning has been increasingly used in recent technologies supporting cybersecurity. This research paper reviews literature on the impact of AI on cybersecurity.
Keywords: Cybersecurity; AI; Machine learning; Threats